1991
DOI: 10.1002/masy.19910460142
|View full text |Cite
|
Sign up to set email alerts
|

Local control of antibody binding to hapten‐presenting interfaces: Steric and electrostatic interaction

Abstract: The binding of labeled antibodies to hapten substituted monolayers at the air/water interface has been studied by means of fluorescence microscopy. Haptens with various spacer lengths between the epitope and a hydrocarbon chain, anchoring the molecule to the interface, have been synthesized. With DMPC,a unspecific binding has been shown to predominate over specific binding due to electrostatic interactions. At high surface pressures the bound antibody is detached because of steric interference with the lipid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…These results indicate that the majority of the measured fluorescence on both types of monolayer surfaces was due to F-(ANO2 Fab) that was membrane bound, rather than in solution but within the finite depth ofthe evanescent field. Although some weak, nonspecific adsorption to the monolayer surfaces presumably occurred even when the F-(ANO2 Fab) haptenbinding sites were occupied, consistent with other reports (Piepenstock et al, 1991), the measured fluorescence in the absence of soluble hapten was much higher, indicating that the majority of the bound F-(ANO2 Fab) in the absence of DNP-G was attached to the surface via the antigen binding region.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These results indicate that the majority of the measured fluorescence on both types of monolayer surfaces was due to F-(ANO2 Fab) that was membrane bound, rather than in solution but within the finite depth ofthe evanescent field. Although some weak, nonspecific adsorption to the monolayer surfaces presumably occurred even when the F-(ANO2 Fab) haptenbinding sites were occupied, consistent with other reports (Piepenstock et al, 1991), the measured fluorescence in the absence of soluble hapten was much higher, indicating that the majority of the bound F-(ANO2 Fab) in the absence of DNP-G was attached to the surface via the antigen binding region.…”
Section: Resultssupporting
confidence: 90%
“…Previous work has shown that anti-dinitrophenyl (DNP) monoclonal antibodies can bind to these planar model membranes if they contain DNP-conjugated phospholipids. The ability of anti-DNP antibodies to bind to the membrane surfaces and the subsequent spatial arrangements and lateral and rotational mobilities of the bound antibodies are sensitive functions of the physical and chemical properties of the membranes (e.g., Piepenstock and Losche, 1991;Timbs et al, 1991; Pisarchick and Tamm, 1988;Subramaniam et al, 1986;Kimura et al, 1986;Uzgiris and Kornberg, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, from DSC experiments on DPPC dispersions it was concluded that the lipid head group contains five firmly bound water molecules in the L. phase (31). Independent support for our result of a large penetration depth of the head group into the water subphase comes from studies of antibody binding to haptens anchored within DPPC monolayers (32). A systematic variation of the spacer length, 1, between the surface and the epitope that binds to the antibody showed that no specific binding occurs for 1 = 6 A.…”
Section: Discussionsupporting
confidence: 59%